Research progress of antibody coupling technique in targeted drug delivery - Meng Li; Tiantian Wang; Dan Tan; Mengqi Wang; Changhai Lei; Yuqing Wang; Shi Hu (Interdisciplinary Medicine)
Abstract Antibody‐drug conjugates are a cutting‐edge biotechnology recently attracting wide attention in the medical field. Binding antibodies to drug molecules could deliver drugs precisely to the site of the lesion, which shows great potential in the treatment of tumors and immune diseases. In this paper, we outlined the current popular antibody‐coupling techniques and summarized various common antibody‐coupling techniques, including antibody‐coupled small toxic molecules, antibody‐coupled oligenucleotides, antibody‐coupled cells, and antibody‐coupled polymers. It provided a new therapeutic strategy and means for targeted drug delivery technology. Finally, we discussed the challenges and future development of the antibody‐drug conjugates.